Lite-Ta
Lonely_Geezer
 
 
\left(x-1\right)\left(x+3\right) x = a_0 + \frac{1}{a_1 + \frac{1}{a_2 + \frac{1}{a_3 + a_4}}} \sum_{i=1}^{n}{X_i^2} e^{i \theta} \vec{F}=m \frac{d \vec{v}}{dt} + \vec{v}\frac{dm}{dt} \oint \vec{F} \cdot d\vec{s}=0 \lim_{x \to a} \frac{f(x) - f(a)}{x - a} \begin{pmatrix}
a_{11} & a_{12} & a_{13}\\
a_{21} & a_{22} & a_{23}\\
a_{31} & a_{32} & a_{33}
\end{pmatrix} \cos^{-1}\theta \bigcap_{i=1}^{n}{X_i} \bigcup_{i=1}^{n}{X_i} X_1, \cdots,X_n x = a_0 + \frac{1}{a_1 + \frac{1}{a_2 + \frac{1}{a_3 + a_4}}} \sum_{i=1}^{n}{X_i} x = a_0 + \frac{1}{\displaystyle a_1 + \frac{1}{\displaystyle a_2 + \frac{1}{\displaystyle a_3 + a_4}}} \sqrt{\frac{x^2}{k+1}}\qquad
x^{\frac{2}{k+1}}\qquad
\frac{\partial^2f}{\partial x^2} \oint \vec{F} \cdot d\vec{s}=0 \mathbf{X} = \left(
\begin{array}{ccc}
x_1 & x_2 & \ldots \\
x_3 & x_4 & \ldots \\
\vdots & \vdots & \ddots
\end{array} \right) A\underset{0}{\overset{a}{\rightleftharpoons}}B 2H_2 + O_2 {\overset{n,m}{\longrightarrow}} 2H_2O e^{i \theta} x = a_0 + \frac{1}{a_1 + \frac{1}{a_2 + \frac{1}{a_3 + a_4}}} x = a_0 + \frac{1}{\displaystyle a_1 + \frac{1}{\displaystyle a_2 + \frac{1}{\displaystyle a_3 + a_4}}} \frac{x-\mu}{\sigma}
Currently Offline
Recent Activity
369 hrs on record
last played on 21 Feb
254 hrs on record
last played on 18 Feb
4.5 hrs on record
last played on 15 Feb